Risk of invasion of the crazy ant Nylanderia fulva (Hymenoptera: Formicidae) in Ecuador - Ferrer-Sánchez, Yarelys; Plasencia Vázquez, Alexis Herminio; Gordon Gómez , Akean Luis; Abasolo-Pacheco, Fernando (Ecosistemas y Recursos Agropecuarios, 2025)
Nylanderia fulva is an aggressive invasive ant that has entered continental Ecuador and constitutes an ecological and economic threat because it reduces arthropod diversity, especially in native ant assemblages. In the present work, the potential geographic distribution of N. fulva in Ecuador was modeled to identify the areas of greatest risk for its potential invasion. Records of the ant’s presence worldwide and in Ecuador were compiled and its potential geographic distribution was modeled with the maximum entropy algorithm using bioclimatic variables. The favorable area for the ant in Ecuador was 110 227 km2, distributed in a large part of the Coastal and Amazon region, areas with tropical climate and climatic conditions like the native and invasive region of the species. Within these suitable sites, the regions with the highest favorability extend only in 18 892 km2 bordering the highlands in the northern and southern portion, representing 17% of the areas with suitable conditions in the country. Much of the country’s biodiversity is concentrated in the coastal and Amazonian region of Ecuador and the crazy ant could move to warmer and drier places due to its potential to colonize new areas, which implies a call for attention to the Ecuadorian authorities. It is necessary to establish a plan to monitor the progress of the invasion of N. fulva in Ecuador, especially with a scenario of climate change that could facilitate its colonization.